2014
DOI: 10.1126/science.1248292
|View full text |Cite
|
Sign up to set email alerts
|

Strong Increase of T c of Sr 2 RuO 4 Under Both Tensile and Compressive Strain

Abstract: A sensitive probe of unconventional order is its response to a symmetry-breaking field. To probe the proposed p(x) ± ip(y) topological superconducting state of Sr2RuO4, we have constructed an apparatus capable of applying both compressive and tensile strains of up to 0.23%. Strains applied along ⟨100⟩ crystallographic directions yield a strong, strain-symmetric increase in the superconducting transition temperature T(c). ⟨110⟩ strains give a much weaker, mostly antisymmetric response. As well as advancing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
290
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 333 publications
(312 citation statements)
references
References 38 publications
12
290
2
1
Order By: Relevance
“…The [100] strain results shown in Ref. 30 at first glance appear quantitatively different from our P [100] results: it was found that T c is gradually enhanced and reaches only 1.9 K at −0.23% strain, which corresponds to 0.21 GPa stress in our experiment, according to an estimation using the elastic constants in Refs. 22 and 23.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The [100] strain results shown in Ref. 30 at first glance appear quantitatively different from our P [100] results: it was found that T c is gradually enhanced and reaches only 1.9 K at −0.23% strain, which corresponds to 0.21 GPa stress in our experiment, according to an estimation using the elastic constants in Refs. 22 and 23.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, the effectiveness of P [100] in inducing the higher-T c SC phase observed in this study is clear and consistent with the results of the uniaxial strain experiments. 30 Notably, the effect of P [100] in inducing the higher-T c SC phase is greater in pure Sr 2 RuO 4 (this study) than in typical Sr 2 RuO 4 -Ru eutectic crystal (Ref. 35): for example, the diamagnetic susceptibility at 2.5 K reaches ∼ 10% at only 0.05 GPa in pure Sr 2 RuO 4 , whereas it is only 5% at 0.45 GPa in the eutectic crystal.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations